PENGARUH MODEL PEMBELAJARAN COOPERATIVE LEARNING TIPE TAKE AND GIVE TERHADAP KEMAMPUAN MENGANALISIS MATERI SEJARAH SISWA KELAS X AKUNTANSI SEMESTER GENAP SMKN 1 METRO - Yeni Purwaningsih; Bobi Hidayat (Swarnadwipa, 2017)
The purpose of this study to determine the effect of type Cooperative Learning model of Take and Give to the ability to analyze the historical material class X SMK 1 Metro Accounting Academic Year 2016-2017. This research uses quasi-experimental research (Quasi Exsperiment), while the design (design) research used in this study is Nonequivalent control group design. The population in this study were all students of class X Accounting for the second semester of SMK Negeri 1 Metro, research using sampling methods Rondom Cluster Sampling. In this study using a model Cooperative Learning type Take and Give in the experimental class are positive and significant effect on students' ability to analyze the historical material Class X Accounting 2 SMK Negeri 1 Metro. Based on analysis of the findings of the use of Cooperative Learning type Take and Give the students the ability to analyze the historical material which has been obtained, it is concluded that the model of Cooperative Learning type selected Take and Give positive effect of increasing students' ability to analyze the historical material.